2022
DOI: 10.1021/acs.jpcc.1c09034
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light Absorbing Silver-Coated Hollow Gold Nanostars for Surface-Enhanced Raman Scattering Detection of Bovine Serum Albumin Using Capping Ligand Exchange

Abstract: Two novel urchinlike plasmonic nanostructures, hollow gold nanostars (HNSs) and silver-coated hollow gold nanostars (AgHNSs), were synthesized using hollow gold nanospheres (HGNs) as templates. The particle morphology was assessed by transmission electron microscopy (TEM), optical properties were characterized by UV–vis spectroscopy, and elemental composition was evaluated by both inductively coupled plasma-optical emission spectrometry (ICP-OES) and energy-dispersive X-ray (EDX) analysis. Both the HNSs and Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…More recently, we have used them as an effective substrate for the realization of SERS nanotags for determination of fibroblast activation protein in fibroblasts. Moreover, it has also been demonstrated that the addition of a silver shell to branched gold nano-objects can further enhance their SERS responses, and that the enhancement is strictly connected to the extent of the silver layer [ 24 , 25 , 26 , 27 ]. Inspired by these works, we decided to apply a silver coating layer to our Triton based GNS to increase their SERS response towards environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have used them as an effective substrate for the realization of SERS nanotags for determination of fibroblast activation protein in fibroblasts. Moreover, it has also been demonstrated that the addition of a silver shell to branched gold nano-objects can further enhance their SERS responses, and that the enhancement is strictly connected to the extent of the silver layer [ 24 , 25 , 26 , 27 ]. Inspired by these works, we decided to apply a silver coating layer to our Triton based GNS to increase their SERS response towards environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high-quality SERS signals, it is essential to design and control the size and morphology of these nanostructures to obtain superior SERS sensitivity, uniformity, and reproducibility. In particular, both experimental results and theoretical calculations indicate that branched Au NPs (such as nanoflowers, nanourchins, nanodendrites, and nanostars) with sharp tips, edges, and corners have intrinsic hotspots, which can generate extremely high electromagnetic field enhancements, [12][13][14] allowing their use in SERS, 15,16 sensing, 17 and photothermal therapy. 18,19 On the other hand, these branched Au NPs have a unique branched structure, which provides a large surface area and numerous sharp tips that can greatly enhance the Raman signal of molecules adsorbed on their surface.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various metal nanoparticles reported to date, anisotropic gold nanostars (GNS) promise to be a potential candidate due to their excellent SERS enhancement properties, tunable plasmon resonance, and good stability in ambient conditions. [29][30][31][32][33] Anisotropic GNS is an excellent SERS platform than other nanoparticle systems owing to three reasons. First, GNS has 3D sharp protruding spikes, thereby facilitating the generation of multiple hot spots than other nanoparticle systems such as nanospheres, nanorods, and nanocubes.…”
Section: Introductionmentioning
confidence: 99%